ENGLISH AS A MEDIUM OF INSTRUCTION: CHALLENGES AND OPPORTUNITIES FOR STUDENTS AND PROFESSORS OF PUBLIC HIGHER EDUCATION INSTITUTIONS IN BRAZIL: - Tenório Fernando, Jorge (Revista CBTecLE, 2022)
This article examined the implications of using English as lingua franca to teach regular and technical disciplines on undergraduate level in Brazil with the objective of identifying both benefits and difficulties encountered by the students and teachers involved. The theoretical background was built upon the concept of English as a medium of instruction – EMI – which has been increasingly adopted by colleges and universities in various countries whose native language is not English. The methodology consisted in developing a syllabus for a common discipline, then have it delivered to students at São Paulo State Technological College (FATEC), and later, at the end of the semester, grade their performance and collect their personal view about the experience. Results showed the project was successful given the students’ effective learning of technical subjects as well as evidence of their English skills improvement, which were both confirmed by them as takeaways in the feedback session.